Earthquake analysis of IBS for double storey housing [electronic resource] - 343471 Nur Fatimah Marwar (Skudai : Universiti Teknologi Malaysia, 2007)
Thesis (Sarjana Kejuruteraan (Awam - Struktur)) - Universiti Teknologi Malaysia, 2007